THE INFLUENCE OF ANCHORING BIAS IN INSTAGRAM ADSON THE PERCEPTION OF UNIVERSITAS NEGERI MEDAN STUDENTS - Niaarota Buulolo; Mika Rafael Kataren; Rita Hartati (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2025)
This study investigated how anchoring bias techniques shape university students' perceptions of Instagram advertisements. We analyzed the persuasive effects of common anchoring strategies, including price contrasts, urgency cues, and scarcity messages. Using a mixed-methods approach, we surveyed 30 students from Universitas Negeri Medan, who evaluated four Instagram ad brochures and answered a series of open-ended questions. The findings revealed a strong persuasive effect: 80% of participants reported they were more likely to purchase after seeing the ads , and an overwhelming 90% identified price discounts as the most compelling element. Furthermore, over half of the respondents (56%) felt that the language used in the ads created a pressure to buy. While many students recognized the persuasive tactics at play, the majority still found the advertisements convincing. This research demonstrates that anchoring bias is a powerful tool in influencing consumer perception, particularly on a visually rich platform like Instagram.